Science, Information, and Policy Interface for Effective Coastal and Ocean Management - Jansson, Julia (Taylor & Francis, 2016)
Science, Information, and Policy Interface for Effective Coastal and Ocean Management presents a wealth of knowledge that enhances current best practices to achieve more effective communication and use of marine environmental information. Useful to all major groups in the policy-making process, from senior policy- and decision-makers to practitioners in coastal and ocean management, it helps to increase understanding of catalysts and barriers to communicating research findings. It also serves as a starting point for further research and progress in efficient marine environment management.